Women Literacy and Infant Feeding Practices in Rural Integrated Child Development Scheme (ICDS) Block of Delhi - Davey , Sanjeev; Davey , Anuradha (National Journal of Community Medicine, 2012)
Background: Infant feeding practices have significant effect on the child nutrition, which largely dependent upon the mothers correct knowledge and awareness for the same. Objective: To find out effect of rural women empowerment through literacy on infant feeding practices in an ICDS block. Material and Methodology: Interview of the mothers of registered children up to 6 years in the rural ICDS block for the feeding practices and recording of the weight of those registered children by the salter weighing scale for their nutritional status. Results: Three fourth of the children had received ceremonial feed in the form of honey or gutti and 40 percent of the mothers in our study has discarded colostrums, considering it as ‘bad milk’. Exclusive breast feeding was received by 34.6% children. As literacy level of mothers increased the nutritional status of children was better. This could be because most of the women who are middle school passed or above are non working, so are able to give more time for care and feeding practices. The Severe malnutrition (grade III and IV) was evident only in illiterate category of mothers, where 58.7% women were working in unskilled or semiskilled job outside home. Conclusion: Women living in chronic hunger are forced to unskilled jobs for income generation for the family, thereby influencing the feeding practices of their children. In such scenario AWCs and AWWs can be a unique opportunity with their focused approach to take care of severe and moderate malnutrition.